Pengaruh Pertumbuhan Ekonomi, Pendapatan Asli Daerah, dan Perimbangan Keuangan Daerah terhadap Pengalokasian Anggaran Belanja Modal Daerah (Pemerintah Kabupaten Bogor) - Setiawan, Hendra; Saputra, Tunggal Ika (Institut Bisnis dan Informatika Kesatuan, 2018)
This research is purposed to determine whether the Economic Growth District Own Source Revenue and Fiscal balance transfers from the centr government to regions significantly affect Capital Expenditure Budget Allocatio Region in Bogor District. The research method used is descriptive method using secondary data obtained from the Central Bureau of Statistics of Bogor and the Office of Financial Management and Expenditure Bogor District. Data collecting methods applied in this study are documentation and literature studies with a quantitative approach. The analysis performed in this study is using bivariate correlation analysis - Pearson correlation, due to data showing their mutual relations. Once data is collected, the data were analyzed using SPSS to test Economic Growth, District Own Source Revenue and Fund Balance significantly related to the Capital Expenditure either partially with significance test correlations and simultaneously. The analysis tool used is using the SPSS (Statistics Product and Service Solution) version 22. Results from this research showed that variables Economic Growth has a significance value of 0.041, which sig. below 0.05, so the variables Economic Growth partially related to the Capital Expenditure and had a positive correlation coefficient of 0.894, which means having a strong correlation. Variable District Own Source Revenue has a significance value of 0.010, which sig. below 0.05, so the variable District Own Source Revenue partially related to the Capital Expenditure and had a positive correlation coefficient of 0.960, which means having a strong correlation. Variable Balance Fund has a significance value of 0.005, which sig. below 0.05, so the variable Balance Fund partially related to the Capital Expenditure and had a positive correlation coefficient of 0.974, which means having a strong correlation.Based on the testing that was done on the Economic Growth, District Own Source Revenue, and Fund Balance acquired the R value of 0.996, which means jointly independent variable is interconnected with the Capital Expenditure budget allocations